2018
DOI: 10.2196/12274
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Available Mobile Apps for Caregivers of People With Alzheimer Disease or Other Related Dementias: Systematic Search

Abstract: Background More than 15 million Americans provide unpaid care for persons with Alzheimer disease or other related dementias (ADRD). While there is good evidence to suggest that caregivers benefit from psychosocial interventions, these have primarily been delivered via face-to-face individual or group format. Alternatively, offering electronic health (eHealth) interventions may assist caregivers in providing quality care while remaining in good health. Research to date has generated little knowledg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…Similarly, the findings of both Choi et al [ 22 ] and Guo et al [ 45 ] reported that apps scored lowest on engagement, reporting just-below minimally acceptable quality and above minimally acceptable quality, respectively. These findings further confirm previous research that evaluated 8 commercially available apps for ADRD care partners and found that the majority provided mostly text-based information [ 48 ]. Below acceptable engagement scores are concerning, as engagement issues can lead to technology abandonment, reduced acceptance, or failure to use the app to its full potential [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the findings of both Choi et al [ 22 ] and Guo et al [ 45 ] reported that apps scored lowest on engagement, reporting just-below minimally acceptable quality and above minimally acceptable quality, respectively. These findings further confirm previous research that evaluated 8 commercially available apps for ADRD care partners and found that the majority provided mostly text-based information [ 48 ]. Below acceptable engagement scores are concerning, as engagement issues can lead to technology abandonment, reduced acceptance, or failure to use the app to its full potential [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 90%
“…This modality addresses barriers to caregiver participation (eg, in-person, synchronous format, time commitment, and cost) for a more feasible, scalable, and cost-effective intervention to reduce stress among this high-need population. The HMP app adapted for caregivers of persons with ADRD seeks to address this clinical gap by testing a no-cost mobile app to reduce stress, emotional distress, and sleep difficulties [ 40 ]. This protocol describes an entirely remote, single-blind feasibility, proof-of-concept RCT of HMP versus a time- and dose-matched educational control (WA) in stressed caregivers of persons with ADRD.…”
Section: Discussionmentioning
confidence: 99%
“…In qualitative studies, caregivers express interest in using mobile apps for stress management and health information [ 35 ] including to learn mindfulness meditation for stress management [ 36 - 39 ]. To the best of our knowledge, there are no consumer-based mobile apps with proven efficacy in decreasing stress, emotional distress, and sleep difficulties among caregivers of persons with ADRD [ 40 ]. Although mindfulness-based mobile apps show promise for helping caregivers of persons with ADRD decrease stress, emotional distress, and sleep difficulties, additional research is needed to establish feasibility and efficacy before widespread dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Deve-se esperar que uma plataforma informativa para o cuidado de idosos com demência apresente padrão de uso fácil e intuitivo, principalmente considerando a heterogeneidade de seus usuários, para que seja simples e acessível para todos aqueles que se dispuserem a utilizá-la. Segundo Wozney et al (2018), as questões relacionadas aos recursos de acessibilidade como tamanho da fonte, cores, contraste, comando de voz, feedback tátil (vibração), aviso sonoro, bem como uma interface amigável, vem sendo apontadas como condições básicas para que o uso de uma plataforma digital seja implementada no cotidiano de um cuidador. Segundo o autor, cerca de 40% dos cuidadores utilizam algum tipo de aplicativo para auxiliar na gestão do cuidado.…”
Section: -O Uso Da Tecnologia Móvel Para Apoiar O Cuidadounclassified
“…Por isso, cuidar da fonte das orientações disponibilizadas no Cuidador-Pro foi uma preocupação para garantir a qualidade do conteúdo. Em estudo desenvolvido por Wozney et al (2018), os autores analisaram os aplicativos com foco no cuidado da pessoa com demência e, entre os dados discutidos, está a falta de declaração de quais orientações científicas os desenvolvedores seguiram para a concepção do conteúdo, o que se torna essencial ao considerarmos a realidade dos dias de hoje.…”
Section: -O Uso Da Tecnologia Móvel Para Apoiar O Cuidadounclassified